Allelic frequencies of NR6A1 and VRTN, two genes that affect vertebrae number in diverse pig breeds: A study of the effects of the VRTN insertion on phenotypic traits of a Duroc × Landrace–Large White cross. (February 2015) - Burgos, Carmen; Latorre, Pedro; Altarriba, Juan; Carrodeguas, José Alberto; Varona, Luis; López-Buesa, Pascual
Abstract: A SNP (748 C > T) in the NR6A1 gene and an insertion (g.20311_20312ins291) in the VRTN gene have been shown to affect vertebrae number in the pig. The allelic frequencies of both genes were investigated in six western breeds and the effects of the VRTN insertion on some phenotypic traits in a Duroc × Landrace/Large White cross. The NR6A1 c. 748T allele, associated with higher number of vertebrae, appeared to be fixed in most studied breeds except in Iberians. The VRTN insertion (Ins allele) shows ample variability in all studied breeds although the allelic frequency of Ins seems to be larger in breeds with a greater history of genetic selection. Ins is associated with an increase in weight at slaughter, in loin and rib primal cut proportions, and with modified meat quality properties such as cooking loss, intramuscular fat content or yield after curing. We discuss the usefulness of both gene markers for pig selection. Highlights: NR6A1 748 C > T is fixed in most Western breeds that have been studied, but not the Iberian breed. VRTN (g.20311_20312ins291) appears at different allelic frequencies in most breeds. We have designed a RT-PCR protocol to analyze NR6A1 748 C > T. VRTN (g.20311_20312ins291) modifies several phenotypic properties of the loin.